Hybrid energy harvesting enabled by a covalent organic framework membrane - Jiaming Yi; Zhuozhi Lai; Qing Guo; Zhiwei Xing; Qi Sun (Advanced Membranes)
The integration of water and thermal energy harvesting presents a promising solution to the intermittency issues associated with individual energy sources. In this study, we show a covalent organic framework (COF) membrane featuring subnanometer, one-dimensional ionic channels, which demonstrate remarkable stability in both acidic and saline environments. The membrane exhibits exceptional permselectivity across various electrolyte solutions, enabling efficient osmotic energy harvesting from proton gradients via reverse electrodialysis. Under a 50-fold concentration gradient of H2SO4, the membrane achieved a peak output power density of 97.1 ​W ​m−2. Furthermore, the membrane facilitates thermo-osmotic energy conversion by selectively screening ionic charges driven by combined salinity and temperature gradients. Under simulated estuarine salinity conditions and a 30 ​K temperature gradient, the COF membrane achieved a maximum output power density of 91.4 ​W ​m−2—an 18-fold increase compared to the commercial benchmark (5 ​W ​m−2). This study underscores the significant potential of COF membranes for efficient energy conversion, enabling the effective harvesting of untapped osmotic and low-grade heat energy.